Preliminary analysis of global column-averaged CO 2 concentration data from the spaceborne aerosol and carbon dioxide detection lidar onboard AEMS - Fan, Chuncan; Chen, Cheng; Liu, Jiqiao; Xie, Yuan; Li, Ke; Zhu, Xiaopeng; Zhang, Lu; Cao, Xifeng; Han, Ge; Huang, Yongjian; Gu, Qianrong; Chen, Weibiao (Optics express, 2024)
In contrast to the passive remote sensing of global CO 2 column concentrations (XCO 2 ), active remote sensing with a lidar enables continuous XCO 2 measurements throughout the entire atmosphere in daytime and nighttime. The lidar could penetrate most cirrus and is almost unaffected by aerosols. Atmospheric environment monitoring satellite (AEMS, also named DQ-1) aerosol and carbon dioxide detection Lidar (ACDL) is a novel spaceborne lidar that implements a 1572 nm integrated path differential absorption (IPDA) method to measure the global XCO 2 for the first time. In this study, special methods have been developed for ACDL data processing and XCO 2 retrieval. The CO 2 measurement data products of ACDL, including the differential absorption optical depth between the online and offline wavelengths, the integral weighting function, and XCO 2 , are presented. The results of XCO 2 measurements over the period from 1 st June 2022 to 30 th June 2022 (first month data of ACDL) are analyzed to demonstrate the measurement capabilities of the spaceborne ACDL system.